Competitive Russia : Foresight Model of Economic and Legal Development in the Digital Age : Proceedings of the International Scientific Conference in Memory of Oleg Inshakov (1952-2018) /: Foresight Model of Economic and Legal Development in the Digital Age : Proceedings of the International Scientific Conference in Memory of Oleg Inshakov (1952-2018). (2020) - Unknown
No abstract available